Iraqi Feminism in Translation: an Analytical study of The Waiting List - Falah Hussein Hanoon Al-Sari ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This research draws critical attention to the translation of The Waiting List, a novel by Iraqi writer, poet, and novelist Daizy Al-Amir. It shows how Parmenter renders Al-Amir’s feminist voice into English preserving the poetic style, metaphorical language, and emotive language of her text. The title itself suggests the central theme of this novel – women’s alienation. It explores diverse ways in which the female characters experience alienation, be it from their families, communities, or even from themselves. This theme is particularly poignant given the historical and social context of Iraq, where women often face marginalization and oppression. Moreover, this study explores how much of the original work survives Parmenter’s translation concerning the notion of cultural loss in translation. Translating voices, such as Al-Amir’s, is important because it provide readers around the world with access to a culturally specific feminist perspective that may otherwise go unheard of due to language and geographical barriers. Feminist translation approaches seek to challenge patriarchal power dynamics, promote gender equality through language, and ensure accurate translations with consideration for cultural context. By acknowledging and addressing these issues, feminist translators create translations that not only convey meaning but also work towards a more equitable world.